2011
DOI: 10.1088/0953-8984/23/6/065102
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of silica coated spindle-type hematite particles

Abstract: Magnetic properties of particles are generally determined from randomly oriented ensembles and the influence of the particle orientation on the magnetic response is neglected. Here, we report on the magnetic characterization of anisotropic spindle-type hematite particles. The easy axis of magnetization is within the basal plane of hematite, which is oriented perpendicular to the spindle axis. Two standard synthesis routes are compared and the effects of silica coating and particle orientation on the magnetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 43 publications
7
70
1
Order By: Relevance
“…This behavior can be attributed to superparamagnetic relaxation and is in perfect agreement with a previous study. 16 The superparamagnetic relaxation at room temperature for the silica-coated particles is unexpected, since it is normally observed for particles with diameter <30 nm only. 23 The investigated particles have formed by aggregation of subunits with a typical size of 10 nm, as suggested by Ocaña et al 9 This indicates that these subunits set the length scale relevant for the magnetic properties and, in particular, for the superparamagnetic relaxation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This behavior can be attributed to superparamagnetic relaxation and is in perfect agreement with a previous study. 16 The superparamagnetic relaxation at room temperature for the silica-coated particles is unexpected, since it is normally observed for particles with diameter <30 nm only. 23 The investigated particles have formed by aggregation of subunits with a typical size of 10 nm, as suggested by Ocaña et al 9 This indicates that these subunits set the length scale relevant for the magnetic properties and, in particular, for the superparamagnetic relaxation.…”
Section: Discussionmentioning
confidence: 98%
“…The existence of pores is confirmed by TEM images (see inset of Figure 2) and is in agreement with observations made on similar particles. [15][16][17] The porosity reduces the effective scattering length density F c . The values for the scattering length densities F water ) 0.946 × 10 -3 nm -2 and F hem ) 4.16 × 10 -3 nm -2 were calculated based on the densities d water ) 1.0 g/cm 3 and d hem ) 5.26 g/cm 3 and were used as fixed parameters.…”
Section: Form Factor Of Porous Core-shell Spindle-type Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] A thorough understanding of bulk hematite's exotic magnetic properties such as anisotropic super-exchange, 4,5 low anisotropy, 6 and unusual spin structure 7 was already achieved by the mid-1960s. 1 More recently, there has been renewed interest in hematite systems at nanometer dimensions for applications in biomedical nanoparticles, 8,9 spin valves, [10][11][12] and chemical sensors. 13 Based on the work of Dzyaloshinsky 4 and Moriya, 5 the magnetic structure of hematite can be explained due to anisotropic super-exchange of the Dzyaloshinsky-Moriya (DM) form, 4,5 together with nearly zero net-uniaxial anisotropy due to the cancellation of the first-order single ion and dipolar anisotropies.…”
Section: Introductionmentioning
confidence: 99%
“…S3 in ESI †). We found that as the conversion time increases, the saturation magnetization (SM) of these hybrid particles steeply increases from a lower value of around SM ≈ 0.12 Am 2 kg −1 for pure hematite particles 42,44 until it levels off at a value SM ≈ 72 Am 2 kg −1 , which corresponds to the expected value for pure maghemite ( Fig. 1(f )).…”
Section: Resultsmentioning
confidence: 61%